Menguatkan Karakter Kerukunan Masyarakat Multikultural Indonesia Melalui Praktik Pendidikan Kewarganegaraan Global di Kota Salatiga - Harto, Giri; Komalasari, Kokom; Nugraheni, Edwindha Prafitra (Program Studi PPKn FIS UNJ & Asosiasi Profesi PPKn Indonesia, 2023)
Indonesia is known as a multicultural nation. This progress is a cultural property as well as prone to horizontal and vertical conflicts. One of the goals of Global Citizenship Education is peace and justice for global citizens. One area in Indonesia that has harmony in accordance with the vision of Global Citizenship Education is the City of Salatiga, Central Java Province. The research method used is qualitative using a case study approach. Based on research results, the people of Salatiga have been very concerned about religious and socio-cultural harmony since ancient times until now. In addition, a life of harmony is the implementation of UNESCO's Sustainable Development Goals (SDGs) program, namely programs of peace, justice and strong institutions. The strategy for increasing harmony is carried out by the community by establishing three civic sites, namely Pancasila Village, National Village and Harmony Village. Various socio-cultural activities are carried out by the community to increase the harmony around them. The difference between the three villages is that Pancasila Village was chosen because it has the characteristics of a fairly complete distribution of places of worship and there is a tradition of tolerance in the community. National Village was chosen because the villagers have an awareness of patriotism. While the Harmony Village was chosen because of the characteristics of the villagers living in harmony and religious conflicts rarely occur.